Probabilistic critical excitation for MDOF elastic plastic structures on compliant ground. - Takewaki, Izuru (Earthquake engineering & structural dynamics.)
Earthquake ground motions and their effects on structural responses are very uncertain even with the present knowledge. It is therefore desirable to develop a robust structural design method taking into account these uncertainties. Critical excitation approaches are promising and a new random critical excitation method is proposed for MDOF elastic plastic shear building structures on compliant ground. The power (area of power spectral density (PSD) function) and the intensity (magnitude of PSD function are fixed and the critical excitation is found under these restrictions. In contrast to linear elastic structures, transfer functions and simple expressions for response evaluation cannot be defined in elastic plastic structures and difficulties arise in describing the peak responses except by laborious elastic plastic time history response analysis. Statistical equivalent linearization is used to estimate the elastic plastic stochastic peak responses approximately. The critical excitation responses are obtained for several examples and compared with those of the corresponding recorded earthquake ground motion.